Effectiveness of Topical Honey Application on Wound Healing: Literature Review Study - Tjongarta, Winny; Antono, Widi (Newinera Publisher, 2025)
The purpose of this study was to determine the wound healing process which has several phases. Another alternative for wound healing is to use honey which is known to have many bioactive components that have been proven effective and fast in the wound healing process. The method of writing literature is a literature review using several databases such as Pubmed, Google Scholar, Medline, Ebsco, Hindawi, Science Direct and Cochrane which were published in the last 10 years. The wound healing process has several phases, namely the hemostasis, inflammation, proliferation and remodeling phases. Each phase has its own healing time duration. Honey is a natural product formed from flower nectar and has been used by humans since ancient times around almost 5500 years ago. Honey has various benefits in the health sector. One of the benefits of honey is that it can prevent wound infections and accelerate the wound healing process. One study conducted by Yupanqui et al. stated that honey has natural antimicrobial properties and is a physical barrier at the wound site. Honey can be a topical therapeutic drug that is studied clinically for wound healing that contains antioxidants, antibacterials, antifungals, antivirals and other clinical benefits.